Lateral Deflection of Single Pile due to Lateral Loads in Clay Soils based on The P-Y Curve Method with Finite Difference Solution, ALLPILE Program, and PLAXIS Program - Ba'ist, Ahmad Jirjisul; Upomo, Togani Cahyadi; Apriyatno, Henry; Nugroho, Untoro (Universitas Negeri Semarang, 2019)
The foundation has a function to hold the load in the form of axial load, lateral load and moment. The axial load on the pile foundation is supported by the pole end resistance and pile friction, while the lateral load on the pile foundation is supported by the relation of the blanket area along with the pile with the ground in the lateral direction. Lateral load causes lateral deflection in which the magnitude of deflection must not exceed the permissible lateral deflection limit of 2.54 cm. The determining factors in lateral deflection are the type of pile foundation, soil type, and the magnitude of the force that occurs. The foundation of a single pile in which the number of one pile, when embedded in clay soil, needs to be investigated for the magnitude of lateral deflection that occurs, this is due to the changing nature of the clay when under the influence of high or low water content. The foundation of the pile uses a concrete head with a condition of a free end with a cylindrical shape with a diameter of 60 cm that is not solid with a wall thickness of 10 cm and a compressive strength of concrete of 60 MPa. Clay soil data uses soil drilling test data in Wirosari, Grobogan, Central Java. The planning method used is the finite element method (PLAXIS program) and the finite difference method (py curve and the ALLPILE program) with lateral load variations of 10 kN, 15 kN and 20 kN given to the top end of the pole with the principle of giving trial and error loads. The results of the calculation of the lateral deflection of the pile on the py curve method with a finite-difference resolution, the ALLPILE program, and the PLAXIS program respectively with a lateral load of 10 kN are 0.0629 cm; 1.21 cm; 0.27 cm, lateral loads of 15 kN are 0.0943 cm; 2.13 cm; 0.4051 cm, and a lateral load of 20 kN is 0.1258 cm; 3.14 cm; 0.5402 cm. Thus the lateral deflection load limit is 15 kN, so as not to exceed the permissible lateral deflection limit of 2.54 cm. The recommended method used is the ALLPILE program to better get the level of security from the lateral deflection of the pole when applied in the field